2019
DOI: 10.3390/ijtpp4030022
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Dimensional Analysis of Multistage Helicoaxial Pump for Two-Phase Flow

Abstract: A four stage helicoaxial pump was tested under varying operating conditions. A range of inlet pressures, rotational speeds (3000, 3600 rpm), and gas void fractures (GVFs) were considered for two fluid viscosities. The head developed and power input to run the pump were recorded. Head, power input and efficiency decrease as the GVF increases with best efficiency point (BEP) moving towards lower flow rate conditions. Dimensional analysis was conducted to evaluate the applicability of current affinity laws to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…No matter if the speed of rotation n or the angular velocity ω is taken into account in accomplishing the calculations, the pressure (head) and flow rate of a turbo machine are always set to be dimensionless parameters being proportional to p n 2 D 2 and Q nD 3 [22][23][24][25][26][27]. The authors in [28] suggest newly established equations for determining the coefficients of flow rate and pressure of multistage helico-axial pumps, working with two-phase mixtures of air and water, as a function of the gas void fraction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…No matter if the speed of rotation n or the angular velocity ω is taken into account in accomplishing the calculations, the pressure (head) and flow rate of a turbo machine are always set to be dimensionless parameters being proportional to p n 2 D 2 and Q nD 3 [22][23][24][25][26][27]. The authors in [28] suggest newly established equations for determining the coefficients of flow rate and pressure of multistage helico-axial pumps, working with two-phase mixtures of air and water, as a function of the gas void fraction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fan system's total coefficient of efficiency is also a constant, i.e., η is a constant. These two parameters are determined by using Equations (19) and (28), involving the obtained before regulation system output flow rate.…”
Section: Frequency Regulation Of the Flow Ratementioning
confidence: 99%
“…In gas-liquid two-phase operation, the internal flow of the pump during gas-liquid two-phase operation is extremely unstable, leading to the decrease of its head and efficiency, which affects the normal operation and service life of the pump [13][14][15]. Scholars have found that the flow pattern transition caused by the evolution of bubbles in the flow field is closely related to the operating characteristics of mixed transport pumps, and the gas pockets in the flow field are the direct cause of the onset of surging.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of blade tip clearance, the internal two-phase flow and pressure surging mechanism in a semi-open mixed flow gas-liquid two-phase flow pump are more complicated. However, some studies have pointed out that at high IGVF conditions, the leakage flow in the blade tip clearance can help improve its pressurization ability.In gas-liquid two-phase operation, the internal flow of the pump during gas-liquid two-phase operation is extremely unstable, leading to the decrease of its head and efficiency, which affects the normal operation and service life of the pump[13][14][15]. Scholars have found that the flow pattern transition caused by the evolution of bubbles in the flow field is closely related to the operating characteristics of mixed transport pumps, and the gas pockets in the flow field are the direct cause of the onset of surging.…”
mentioning
confidence: 99%
“…The multi-stage centrifugal pump needs to operate under different inlet gas volume fraction (IGVF) conditions, as the volume fraction of oil and gas always changes during crude oil production and transportation. At low IGVF conditions, the pump has a higher head and efficiency, but under high IGVF conditions, its pressurization capacity drops sharply or it even stops working, which seriously endangers the continuity and safety of industrial production [3]. Therefore, it is of great significance to carry out an investigation on gas-liquid two-phase flow in a multistage centrifugal pump and improve its performance at IGVF conditions.…”
Section: Introductionmentioning
confidence: 99%